PERAN DAN STRATEGI PENGELOLAAN ZAKAT, INFAK, DAN SEDEKAH (ZIS) DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI DI INDONESIA - Susanty Susanty; Irma Malini (Jurnal Ekonomi dan Bisnis, 2024)
Economic growth is one of the main indicators of a country's development success. In the context of Islamic economics, Zakat, Infak, and Sedekah (ZIS) play a crucial role in supporting economic growth and alleviating poverty. This research aims to analyze the role and management strategies of ZIS in improving the economic welfare of the community in Indonesia. The method used is qualitative with a document study approach from various relevant secondary sources. The research results show that targeted distribution of ZIS (Zakat, Infaq, and Shadaqah) can reduce poverty levels, accelerate poverty alleviation, and increase the income of beneficiaries. In addition, institutions like BAZNAS play an important role in the management of ZIS through various economic empowerment programs. Through this program, it is hoped that it can encourage the beneficiaries to continue striving earnestly, with the expectation that they can gradually transform from beneficiaries into contributors.